Developing a pai curriculum that is responsive to diversity - Ida Zahara Adibah; Uswatun Chasanah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine the development of an Islamic Religious Education (PAI) curriculum that is responsive to diversity in Indonesia. As a country with a wealth of culture, ethnicity, and beliefs, the development of the PAI curriculum must be able to accommodate multicultural values ​​while maintaining the essence of Islamic teachings. Using a qualitative approach with a literature study method, this study analyzed various sources of national scientific publications to identify models, strategies, and challenges in developing an inclusive PAI curriculum. The results of the study indicate that the development of an PAI curriculum that is responsive to diversity can be implemented through the integration of multicultural values, adjustment of teaching materials according to the local context, application of participatory learning methods, and increasing teacher competence in managing diversity. This study also identified several challenges such as differences in interpretation of religious texts, limited educational resources, and resistance from conservative groups. The implications of this study suggest the need for reformulation of the PAI curriculum development policy that pays more attention to the socio-cultural aspects of Indonesian society without sacrificing fundamental religious principles.